2019
DOI: 10.1021/acs.chemrev.9b00404
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating Amyloid Aggregates using Fluorescent Probes

Abstract: Amyloids are a broad class of proteins and peptides that can misfold and assemble into long unbranched fibrils with a cross-β conformation. These misfolding and aggregation events are associated with the onset of a variety of human diseases, among them, Alzheimer’s disease, Parkinson’s disease, and Huntington disease. Our understanding of amyloids has been greatly supported by fluorescent molecular probes, such as thioflavin-T, which shows an increase in fluorescence emission upon binding to fibrillar aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
193
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(202 citation statements)
references
References 198 publications
1
193
0
Order By: Relevance
“…Our design strategy is different from most previous studies, which are focused on adjusting optical properties to turn on (off) signals or make larger stokes shis. [9][10][11][12][13] Unfortunately, few probes have been designed based on the insights from the Ab structures. In this report, we demonstrated that our designed small-molecule uorescence probe, ICTAD-1, has the capacity to spectrally differentiate Ab40 and Ab42 in vitro and in the biologically relevant environment.…”
Section: Introductionmentioning
confidence: 99%
“…Our design strategy is different from most previous studies, which are focused on adjusting optical properties to turn on (off) signals or make larger stokes shis. [9][10][11][12][13] Unfortunately, few probes have been designed based on the insights from the Ab structures. In this report, we demonstrated that our designed small-molecule uorescence probe, ICTAD-1, has the capacity to spectrally differentiate Ab40 and Ab42 in vitro and in the biologically relevant environment.…”
Section: Introductionmentioning
confidence: 99%
“…Well‐known examples are Alzheimer's, Parkinson's and Huntington's diseases [2] . To better understand diseases and design drugs, a variety of methods—from biochemical assays to time‐resolved microscopy—have been developed to investigate protein folding [3] and to monitor the self‐assembly of defective proteins into pathogenic protein aggregates [4] . Among them, photoluminescence techniques are highly valuable due to their high sensitivity and the possibility to select, synthesize and optimize a diversity of photoluminescence probes (luminophores).…”
Section: Figurementioning
confidence: 99%
“…Based on the analysis above, we sort out four main criteria which should be satisfied to realize high-performance fluorescent probes for detecting and imaging Aβ fibrils and plaques in vivo at an early stage (Scheme 1B): (1) geometric configurations matching the β-sheet structure; (2) balanced hydrophilicity and hydrophobicity which guarantees the BBB crossing ability and high SNR;…”
Section: Introductionmentioning
confidence: 99%